Conformational landscape of soluble α-klotho revealed by cryogenic electron microscopy - Nicholas J. Schnicker; Zhen Xu; Mohammad Amir; Lokesh Gakhar; Chou-Long Huang (Scientific Reports)
Abstract α-Klotho (KLA) is a type-1 membranous protein that can associate with fibroblast growth factor receptor (FGFR) to form co-receptor for FGF23. The ectodomain of unassociated KLA is shed as soluble KLA (sKLA) to exert FGFR/FGF23-independent pleiotropic functions. The previously determined X-ray crystal structure of the extracellular region of sKLA in complex with FGF23 and FGFR1c suggests that sKLA functions solely as an on-demand coreceptor for FGF23. To understand the FGFR/FGF23-independent pleiotropic functions of sKLA, we investigated biophysical properties and structure of apo-sKLA. Single particle cryogenic electron microscopy (cryo-EM) revealed a 3.3 Å resolution structure of apo-sKLA that overlays well with its counterpart in the ternary complex with several distinct features. Compared to the ternary complex, the KL2 domain of apo-sKLA is more flexible. Three-dimensional variability analysis revealed that apo-sKLA adopts conformations with different KL1-KL2 interdomain bending and rotational angles. Mass photometry revealed that sKLA can form a stable structure with FGFR and/or FGF23 as well as sKLA dimer in solution. Cryo-EM supported the dimeric structure of sKLA. Recent studies revealed that FGF23 contains two KLA-binding sites. Our computational studies revealed that each site binds separate KLA in the dimer. The potential multiple forms and shapes of sKLA support its role as FGFR-independent hormone with pleiotropic functions. The ability of FGF23 to engage two KLA’s simultaneously raises a potential new mechanism of action for FGF23-mediated signaling by the membranous klotho.